Sequential crops for food, energy, and economic development in rural areas: the case of Sicily. (22nd November 2017) - Selvaggi, Roberta; Valenti, Francesca; Pappalardo, Gioacchino; Rossi, Lorella; Bozzetto, Stefano; Pecorino, Biagio; Dale, Bruce E.
Abstract: In this paper, we apply the principles of Biogasdoneright® to agriculture in Sicily (Italy), or more generally to Mediterranean agriculture. We propose new potential crop rotation schemes using Sorghum spp. drip irrigated second harvest and Italian sainfoin (Hedysarum coronarium L.) between two cycles of durum wheat to produce biogas and perhaps biomethane subsequently under the Biogasdoneright system. The Biogasdoneright system is a new model for sustainable biogas production based on sequential cropping and integration with food production. In Sicily, as in other Mediterranean countries, sequential crops and some perennial crops such as Opuntia spp. might be cultivated in environmentally critical areas prone to erosion, desertification, and fires. Therefore, biogas produced according to the crop rotation schemes as illustrated in this paper avoids competition with food and feed crops, while offering to the Sicilian agricultural sector many agronomic, economic, environmental, and social benefits. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd